EFFECTIVENESS OF GUIDED DISCOVERY BASED THERMOCHEMISTRY MODULE TO TRAIN CRITICAL THINKING SKILLS BASED ON GENDER DIFFERENCES - Andini Desikasari Nuraisyah; Sulistyo Saputro; Endang Susilowati (Jurnal Tadris Kimiya, 2020)
Critical thinking skills are important competencies that need to be developed in chemistry learning. This study aimed to determine the effectiveness of the guided discovery-based thermochemistry module in developing critical thinking skills based on gender differences. The subject of this research was 76 females and 20 males of class XI Mathematics and Nature Science from three high schools in Ponorogo, Indonesia. This study used one school for each category, namely high, medium, and low. The research method used a quasi-experimental design with one group pretest-posttest. The data analysis technique used T-test with SPSS 21 software. The result showed that the average increase in student scores or normality gain score (n-gain) was 0.5050 to 0.6362, which means students' critical thinking skills improved after the implementation of guided discovery-based thermochemistry modules. T-test result in high category schools obtained T count > T table (2.142> 2.032), which showed that there are significant differences between the critical thinking skills of female and male students. Meanwhile, T count and T table in medium category school were 1.353 and 2.034, respectively. T count and T table in low category school respectively 1.106 and 2.068. Analysis of T-test results in medium and low school categories can be written -T table < T count < T table, is means there is no significant differences between the critical thinking skills of female and male students. Thus, guided discovery-based thermochemistry modules are effectively applied to high, medium and low school categories.